2020
DOI: 10.1159/000506532
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of Anti-Neutrophil Cytoplasmic Autoantibody-Associated Vasculitis in Patients Over Age 75 Years: A Meta-Analysis

Abstract: Background: The benefits of treating anti-neutrophil cytoplasmic autoantibody-associated vasculitis (AAV) in advancing age remains unclear with most published studies defining elderly as ≥65 years. This study aims to determine outcomes of induction immunosuppression in patients aged ≥75 years. Methods: A cohort of patients aged ≥75 years with a diagnosis of AAV between 2006 and 2018 was constructed from 2 centres. Follow-up was to 2 years or death. Analysis included multivariable Cox regression to compare mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…For specific patient populations, the KDIGO guidelines (, 2024) suggest that the use of RTX is superior to CYC for induction therapy in frail elderly patients, although the specific evidence remains unclear. Meta-analyses ( Morris et al, 2020 ) have shown that in patients with AAV aged 75 and older, the use of CYC or RTX for induction therapy is significantly associated with a lower risk of 2-year mortality. Another multicenter retrospective survival analysis ( Aqeel et al, 2023 ) indicates that CYC, CYC + RTX, and RTX alone are equally effective in inducing remission in AAV patients over the age of 60.…”
Section: Biologicsmentioning
confidence: 99%
“…For specific patient populations, the KDIGO guidelines (, 2024) suggest that the use of RTX is superior to CYC for induction therapy in frail elderly patients, although the specific evidence remains unclear. Meta-analyses ( Morris et al, 2020 ) have shown that in patients with AAV aged 75 and older, the use of CYC or RTX for induction therapy is significantly associated with a lower risk of 2-year mortality. Another multicenter retrospective survival analysis ( Aqeel et al, 2023 ) indicates that CYC, CYC + RTX, and RTX alone are equally effective in inducing remission in AAV patients over the age of 60.…”
Section: Biologicsmentioning
confidence: 99%
“…A recent meta-analysis demonstrated that older adults with AAV had better survival when receiving induction immunosuppression. 21 Recent research has delineated a less toxic but equally effective rituximab-based and steroid-reduced (or steroid-free) treatment regimen [22][23][24][25] that could be an effective way of maintaining disease-modifying treatment while mitigating steroid-associated adverse events.…”
Section: Frailty In Glomerular Disease Treated With Immunosuppressionmentioning
confidence: 99%
“…Bei älteren Patient*innen wurde ein signifikanter Überlebensnutzen bei denjenigen festgestellt, die eine Induktionstherapie erhielten [ 48 ]. Die Intensität der Therapie ist jedoch auf den Gesundheitszustand jeder Person anzupassen.…”
Section: Induktionstherapie Bei Gpa Und Mpaunclassified